2008
DOI: 10.1111/j.1471-4159.2008.05562.x
|View full text |Cite
|
Sign up to set email alerts
|

PLC‐dependent intracellular Ca2+ release was associated with C6‐ceramide‐induced inhibition of Na+ current in rat granule cells

Abstract: 2+ release by dantrolene could not decrease the C 6 -ceramide-induced cell death. We therefore suggest that increased PLC-dependent Ca 2+ release through the ryanodine-sensitive Ca 2+ receptor may be responsible for the C 6 -ceramideinduced inhibition of I Na , which does not seem to be associated with C 6 -ceramide-induced granule neuron death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…Cerebellar GCs grown in primary culture express tetrodotoxin (TTX)-sensitive Na V channels which are responsible for action potentials (APs) and for the code relay in the cerebellar circuitry [16], [17]. Cerebellar GCs are widely used as a model for neuronal cell development and apoptosis [18][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebellar GCs grown in primary culture express tetrodotoxin (TTX)-sensitive Na V channels which are responsible for action potentials (APs) and for the code relay in the cerebellar circuitry [16], [17]. Cerebellar GCs are widely used as a model for neuronal cell development and apoptosis [18][20].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the I Na densities of cerebellar GCs are modulated by the lipid products ceramide and arachidonic acid (AA). Ceramide reduces the I Na of cerebellar GCs by increasing calcium release through the ryanodine-sensitive Ca 2+ receptor [21] while elevation in intracellular AA levels increases the I Na of cerebellar GCs through the PGE 2 -mediated activation of the cAMP/PKA pathway [22]. The present study was conducted to determine whether exposure to ELF-EMF influences the Na + channels of cerebellar GCs and, if so, whether this effect is mediated by changes in ceramide and/or arachidonic acid.…”
Section: Introductionmentioning
confidence: 99%
“…GCs (granule cells) occupy a key position in the cerebellumcortex circuitry, forming the input layer of the major cerebellar afferent system. Cerebellar GCs grown in primary culture express TTX (tetrodotoxin)-sensitive Na V channels that determine the discharge of the GC action potential and the code relayed into the cerebellar circuitry [22,23]. Therefore understanding the mechanisms of how GC Na V channel activity is regulated is of particular importance.…”
Section: Introductionmentioning
confidence: 99%
“…A), which was significantly different from the results obtained without KN‐93 ( P < 0.05), suggesting that the Ca 2+ /CaM pathway is associated with the inhibitory effect of MT on the ELF‐EMF exposure–induced increase in I Na . We then tested the effect on ELF‐EMF exposure–induced increase in I Na by treatment of C 6 ‐ceramide, which increases Ca 2+ release through the ryanodine‐sensitive Ca 2+ receptor . Based on our results, C 6 ‐ceramide could mimic the effect of MT and decreased the ELF‐EMF‐induced inhibitory effect in I Na from 71.2 ± 8.0% to 16.8 ± 11.7% ( n = 11, Fig.…”
Section: Resultsmentioning
confidence: 92%
“…5B). In rat cerebellar GCs, intracellular Ca 2+ is mainly released by the ryanodinesensitive Ca 2+ receptor pathway [35]. Therefore, we used ruthenium A B Fig.…”
mentioning
confidence: 99%